Analisis Jarak Tempuh dengan Menggunakan Sistem Simulasi - Chandra, Agung (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
This research is designed to get the shortest time and distance for Order Picking activities. This activity is categorized as a labor – intensive activity and is the most critical activity in warehouse operation. One way to achieve that is by using the routing method – S-Shape and Return Strategy which are the most common and widely used method by a picker (s). Congestion or queuing factor is included when there are more than one picker and simulated by Warehouse Real Time Simulator (WRTS) and to get the shortest distance by using Warehouse Optimizer (WO). By combining WRTS and WO, the result is shortest distance, shortest time, and optimal man power (picker).